Diakonia Karitatif dan Solidaritas Ekonomi Jemaat : Studi Kisah Para Rasul 2:44–47 - Eddy Susanto; Guntur Hari Mukti; Nira Olyvia Purmanasari (LPPM - STT Kadesi Bogor, 2026)
This study aims to interpret the theological meaning of the practice of sharing in Acts 2:44–47 in relation to the internal economic life of the congregation. The study is motivated by a prevailing understanding of diakonia that tends to position charitable service as an additional activity of the church, without sufficiently relating it to the dynamics of communal fellowship and shared life within the faith community. Employing a qualitative approach through library research, this study conducts a biblical-historical analysis of Acts 2:44–47. The findings indicate that the practice of sharing in the early Christian community represents a form of economic solidarity rooted in communal fellowship and integrated into the congregation’s relational life, rather than merely an incidental act of charity. This economic solidarity possesses theological and contextual limitations and therefore cannot be applied literally to contemporary church contexts without critical reflection. This study contributes to the development of practical theological reflection by positioning the relationship between faith, fellowship, and the economic life of the congregation as an integral component of the understanding of diakonia.